A facile synthesis of Bi@PbS nanosheets and their key physical properties analysis for optoelectronic technology. (1st March 2020) - Shkir, Mohd.; Chandekar, Kamlesh V.; Khan, Aslam; El-Toni, Ahmed Mohamed; AlFaify, S.
Abstract: Herein, the synthesis of pure and Bi-doped PbS (Bi: PbS) nanopowders was attained facilely by the chemical route at low temperature. The presence of Bi content and its homogeneity in the final products was confirmed by EDX/SEM mapping analysis. The presence of a cubic crystal system was confirmed through X-ray diffraction study, and lattice parameters were evaluated. XRD patterns confirmed the absence of extra peaks due to free Bi or any other phase formation in the final products. The crystallite size, density of dislocation, and strain values were also estimated, and the values of the crystallite size were found to lie in a range of 16–24 nm. Vibrational spectroscopy revealed the presence of two phonon-modes as LO, 2LO, and 3LO at 135, 270, 430, and 601 cm −1, respectively, with minute shifts in their positions due to doping and the quantum confinement effect. The surface morphology of nanoparticles (NPs) of size 8–10 nm to nanosheets (NSs) of few microns size assembled from very fine nanoparticles (<10 nm) in Bi doped PbS were remarkably modified based on FE-SEM analysis. The diffused reflectance technique was employed to evaluate the energy gap ( E g d ) of all the final products, which was found to fall in the range of 0.85–1.9 eV, and theses vales were larger than that of bulk PbS, i.e. 0.41 eV. The enhancement in the value of E g d is due to the quantization effect. PL emission spectra recorded at λ e x c = 450 nm possessed three emission bands at approximately 518 ± 10 nm, (green and intense) and 558 ± 2 nm (yellow-green), and 708 ± 2 nm (red and broad). The intensity of the PL emission was quenched with Bi doping; however, it was enhanced for doped PbS containing 2.5 wt% Bi. The dielectric constant was found to be in range of 26–46 overall at the tested frequencies, and the 1.0 wt% Bi: PbS sample attained the maximum value. The total AC conductivity value increased with increasing frequency and obeyed the universal frequency power law, and the 1.0 wt% Bi: PbS attained the maximum value.